Perioperative Management of Non-Small Cell Lung Cancer in the Era of Immunotherapy - Ulas Kumbasar; Erkan Dikmen; Zeliha Gunnur Dikmen; Ates Tenekeci; Ilgen Mender; Sergei Gryaznov; Burak Bilgin; Saadettin Kilickap (Cells)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related mortality worldwide. Nonetheless, deeper molecular understanding of NSCLC has resulted in novel therapeutic approaches, including targeted therapy and immunotherapy, which have improved patient prognosis and outcomes in recent years. Immune checkpoint inhibitors (ICIs), with or without chemotherapy, are now considered valuable components of treatment for NSCLC cases that do not have specific actionable genetic mutations. Patients with actionable genetic mutations are candidates for targeted therapies. The primary focus of this review is the rationale for using ICIs in the perioperative setting for patients with resectable NSCLC and in advanced disease settings. Furthermore, we compare the benefits of using ICIs with the challenges associated with their clinical implementation in resectable and advanced NSCLC. Finally, we emphasize the development of novel treatment strategies that potentially provide an optimal treatment choice for patients with advanced NSCLC.